Optimization of Drainage System on Jalan Sisingamangaraja to Overcome Flooding in Tigalingga Village, Dairi Regency - Natanael Bangun; Cut Nuraini; Abdi Sugiarto (CV. Doki Course and Training, 2026)
Tigalingga Village is one of the areas that, geographically, has a relatively low-lying topography with fairly flat terrain, making it prone to waterlogging, especially during the rainy season. High rainfall, combined with an inadequate drainage system, causes routine flooding at several locations, one of which is along Sisingamangaraja Road. Frequent flooding not only disrupts residents’ daily activities but also causes damage to road infrastructure, hampers transportation, and increases the risk of waterborne diseases. One of the main causes of flooding on Sisingamangaraja Road is the limited capacity of the drainage channels to accommodate heavy rainfall. Many drainage channels are clogged with waste, sedimentation, and other deposits, preventing water from flowing smoothly into rivers or disposal channels. This condition is further exacerbated by the growth of settlements around the road, which increases surface runoff and reduces water infiltration areas. This flooding problem requires structured and sustainable management. One effort that can be undertaken is the construction or improvement of the drainage system along Sisingamangaraja Road by considering flow capacity, channel slope, and the final disposal system. With the development of an effective drainage system, it is expected that waterlogging can be minimized, community mobility will not be disrupted, and the risk of infrastructure damage can be red reduced. In addition, improving drainage quality also plays a role in maintaining environmental quality and public health in Tigalingga Village as a whole. Therefore, the development of the drainage system along Sisingamangaraja Road is not only an infrastructure necessity but also a strategic step in flood risk management and improving the quality of life of the community. This research is important to formulate appropriate technical solutions to address flooding, as well as to serve as a reference for the development of a sustainable drainage system in the village.